2017
DOI: 10.1155/2017/5845849
|View full text |Cite
|
Sign up to set email alerts
|

HIF1A(rs11549465) andAKNA(rs10817595) Gene Polymorphisms Are Associated with Primary Sjögren’s Syndrome

Abstract: Objective. To evaluate the allele and genotype frequencies of polymorphic sites of HIF1A and ANKA genes in primary Sjögren's syndrome (pSS). Methods. We included 110 patients with pSS and 141 ethnically matched healthy controls. Three HIF1A gene polymorphisms (Pro582Ser, Ala588Thr, and C191T) and two AKNA gene polymorphisms (−1372C>A and Pro624Leu) were genotyped using TaqMan probes in a Real-Time PCR instrument. Associations between pSS and genotypes, alleles, and inheritance models of the SNPs of interest we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In total, 21 papers were found as eligible to be included in this scoping review Figure 1 shows 10 observational studies (five cross-sectional studies [ 6 , 22 , 23 , 24 , 25 ] and five cases and controls studies [ 26 , 27 , 28 , 29 , 30 ]) and 11 experimental studies (five in vivo [ 11 , 12 , 13 , 14 , 15 ], three in vitro [ 1 , 5 , 20 ], and three studies featuring both in vitro and in vivo assays [ 16 , 17 , 18 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 21 papers were found as eligible to be included in this scoping review Figure 1 shows 10 observational studies (five cross-sectional studies [ 6 , 22 , 23 , 24 , 25 ] and five cases and controls studies [ 26 , 27 , 28 , 29 , 30 ]) and 11 experimental studies (five in vivo [ 11 , 12 , 13 , 14 , 15 ], three in vitro [ 1 , 5 , 20 ], and three studies featuring both in vitro and in vivo assays [ 16 , 17 , 18 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the number of individuals included, the most widely studied disease related to AKNA was degenerative knee osteoarthritis (KOA) (57.4% of participants in two studies) [ 28 , 30 ]. Two studies investigated the participation of AKNA in other autoimmune diseases, pSS (progressive systemic sclerosis) [ 29 ], and VKH (Vogt–Koyanagi–Harada disease) [ 26 ], representing 6% of all participants, and one publication evaluated disorders associated to chronic respiratory infectious diseases (PCD, primary ciliary dyskinesia) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that HIF1α expressed in epithelial cells protects against hypoxia-induced tight junction integrity loss and epithelial secretory function loss. The genotype and the allele of the HIF1A Pro582Ser polymorphism were associated with a reduced risk of pSS, suggesting that HIF1α activity may be involved in the development of pSS disease ( 24 ). Such different results may be related to different degrees of hypoxia.…”
Section: Characteristics Of the Salivary Gland Microenvironmentmentioning
confidence: 99%
“…The etiology and pathogenesis of SS are still unclear, and it is generally believed that genetic susceptibility related to environmental factors is an important cause of the occurrence of Sjogren’s syndrome ( 10 ). Currently, genome-wide association studies on pSS have been completed, among which HLA genes have the strongest association signal ( 11 ). Epigenetic mechanisms such as DNA methylation, histone modification, and noncoding RNA play a role in the pathogenesis of pSS by regulating gene expression and may form a dynamic link between the genome and phenotypic expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, a good number of single genetic association (SGA) studies also reported the association of these two polymorphisms with other diseases, including type 2 diabetes (T2D), cardiovascular diseases (CVD), lung disease, autoimmune diseases, inflammatory diseases, preeclampsia, osteoarthritis, lumbar disc degeneration, high altitude polycythemia, age-related macular degeneration and many more [ 16 54 ]. The SGA study of Hernández-Molina et al [ 18 ] reported that HIF1A 1772 C/T is a significant genetic factor for autoimmune disease, whereas some other studies [ 25 , 31 ] found its insignificant association. Similarly, some authors showed the significant association of HIF1A (1772 C/T and 1790 G/A) with cardiovascular diseases (CVD) [ 21 , 40 ], though some authors did not find the significant effect in the same question [ 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%